Metabolic alterations in the sera of Chinese patients with mild persistent asthma： a GC-MS-based metabolomics analysis - Chang, Chun; Guo, Zhi-guo; He, Bei; Yao, Wan-zhen (Acta pharmacologica Sinica, 2015)
Aim： To character the specific metabolomics profiles in the sera of Chinese patients with mild persistent asthma and to explore potential metabolic biomarkers. Methods： Seventeen Chinese patients with mild persistent asthma and age- and sex-matched healthy controls were enrolled. Serum samples were collected, and serum metabolites were analyzed using GC-MS coupled with a series of multivariate statistical analyses. Results： Clear intergroup separations existed between the asthmatic patients and control subjects. A list of differential metabolites and several top altered metabolic pathways were identified. The levels of succinate （an intermediate in tricarboxylic acid cycle） and inosine were highly upregulated in the asthmatic patients, suggesting a greater effort to breathe during exacerbation and hypoxic stress due to asthma. Other differential metabolites, such as 3,4-dihydroxybenzoic acid and phenylalanine, were also identified. Furthermore, the differential metabolites possessed higher values of area under the ROC curve （AUC）, suggesting an excellent clinical ability for the prediction of asthma. Conclusion： Metabolic activity is significantly altered in the sera of Chinese patients with mild persistent asthma. The data might be helpful for identifying novel biomarkers and therapeutic targets for asthma.